Medical education system (re)building in a fragile setting: Northwest Syria as a case study. - Yamama Bdaiwi; Safwan Alchalati; Ammar Sabouni; Munzer Al-Khalil; Omer Abdrabbuh; Ahmad Kejah; Abdulhadi Shaban; Mohammad Almousa; Hasan Almarei; Abdalhakem Haj Asaad; Abdulhaseb Alkdro; Mohammed Almoayyad; et al. (Public Library of Science (PLoS), 2023)
Background Syria has witnessed more than a decade of armed conflict through which healthcare workers and facilities have not only been affected, but targeted. Amidst this targeting of healthcare workers, subsequent displacement, and 'weaponization' of healthcare, the medical education and health professional training (MEHPT) of those that remain has split into at least two distinctive contexts: government controlled, and non-government controlled. Efforts to rebuild MEHPT in light of this polarisation and fragmentation have led to a new MEHPT system in non-government controlled northwest Syria, that functions through what we describe as a 'hybrid kinetic model'. This mixed-methods study provides an in-depth analysis of this MEHPT system as a case study to inform future policy planning and interventions in the context of future post-conflict health workforce development. Methods We used mixed methods to investigate the state of MEHPT in northwest Syria during September 2021 and May 2022. This included a) Stakeholder analysis, b) 15 preparatory experts consultations c) 8 Focus group discussions d) 13 Semi-structured interviews e) 2 Questionnaires and f) Validation workshops. Results We identified three main categories of key stakeholders working on MEHPT in northwest Syria: 12 newly established academic institutions, 7 local governance authorities involved in MEHPT, and 12 non-governmental organisations (NGOs). The MEHPT system operated through these stakeholders in a three-layer system to provide undergraduate and postgraduate MEHPT. In the first, top, layer, external NGOs and donors hold the strongest capacity at the expense of relatively under resourced internal governance in the second, middle, level. In the third, bottom, level, local academic bodies operate. We uncovered several levels of challenges facing these stakeholders including governance challenges, institutional challenges, individual challenges, and political challenges. Despite these challenges, participants in our study highlighted significant opportunities within the MEHPT system and that MEHPT can be a peace building pillar for the community. Discussion To our knowledge, this is the first paper that provides an in-depth situational analysis of the MEHPT system in a conflict setting while engaging the voice of local key stakeholders. We found that local actors in MEHPT in non-government controlled northwest Syria have made efforts towards (re)building a new, hybrid and kinetic MEHPT system, through a bottom-up approach. Despite these efforts, the MEHPT system remains fragile and polarised, suffering from several levels of challenges with limited involvement of internal governance. Building on our findings, to improve this approach and build bridges of trust among stakeholders and the MEHPT community, further studies are needed to determine feasible approaches to increasing the role of internal governance structures in the MEHPT system through: 1-Formalisation of efforts through establishing a MEPHT technical coordination unit. 2-Further shifting of power from external supporting NGOs and funders to internal governance structures. 3- Working towards achieving sustainable long-term partnerships.